(NkIRILLO(B-(NMEFODIEWSKIE PEREWODY U @VNYH I WOSTO^NYH SLAWQN (B:s (Nu^EBNOE POSOBIE (B/s - (NlOGA^EW(B, (NkONSTANTIN iWANOWI^s ((Nl(B. :s (Nlgu(B,s, 1988)
(NbIBLIOGR(B.: (NS(B. 80-83 (37 (NNAZW(B.)s
(NmIN(B-(NWO WYS[(B. (NI SRED(B. (NSPEC(B. (NOBRAZ(B. (Nrsfsr(B. (Nlgus
Keywords: (NpAMQTNIKIs; (NpEREWODY NA SLAWQNSKIE QZYKIs; (NrELIGIOZNAQ LITERATURA GRE^ESKAQ DREWNQQs; (NrUKOPISI SLAWQNSKIEs; (NsLAWQNSKAQ PISXMENNOSTX DREWNQQs